British Marxism and Juan Carlos Rodríguez: The Ideological Unconscious Revisited. Issue 4 (1st October 2020) - Read, Malcolm K.
Abstract : In contrast to an Althusserian tradition that, through the work of Juan Carlos Rodríguez, has advanced the concept of the ideological unconscious, British Marxists have proved to be characteristically resistant to "unconsciousness" per se and even repressive of Althusserian variations on the theme. In essence, two traditions of Marxism find themselves in opposition: the first takes as its point of departure the notion of a social formation, articulated on the basis of conflicting modes of production, the second the subject/object dichotomy, which accords priority to subjectivity, individual or collective. Rodríguez theorizes the ideological unconscious through the close analysis of literary texts from which the present essay takes a representative selection. Particularly, the work of E. P. Thompson and Perry Anderson are here considered for their refusal of ideological unconsciousness, notably in its Althusserian guise.